Celostni pristop pri zagotavljanju pomoči na domu - Gjura, Rosana (Socialno delo, 2017)
The increasing growth of the elderly population challenges both social and health care systems with the challenge of increasing demands for long-term care and other services. The Institute for Home Care in Ljubljana has been providing such services since 2002. In addition to the basic activities carried out by social services, it also conducts organized volunteering, and cross-generation co-operation. In May 2015 the Institute, along with its project partners, started the project "Active and quality aging in home environments", which has been co-financed by the Norway Grants Programme. This was carried out to supplement the Institute's core activity, and because of the growing need for certain healthcare services at home. During the project, we worked according to the principles of integrated care and provided our users with free services in physiotherapy, work therapy, nursing, speech pathology, nutritional counselling, measurements of physical and mental abilities and intervention, adaptation of the living environments to the needs of elders and programs of physical exercise. The results of the project are presented in the article.
Keywords: dolgotrajna oskrba; storitve; stari ljudje; Ljubljana; zdravstvena nega; integrirana oskrba